2023
DOI: 10.3390/coatings13010199
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Properties and Corrosion Resistance of Plasma-Sprayed Fish Scale Hydroxyapatite (FsHA) and FsHA-Doped Yttria-Stabilized Zirconia Coatings on Ti–6Al–4V Alloy for Biomedical Applications

Abstract: Hydroxyapatite (HA) coatings on metallic implants have been extensively used in orthopedic applications to improve tissue-implant interactions, enhance their biocompatibility, and enhance their functionality. However, the expensive synthetic HA is the most widely used bioceramic for implant coatings, leading to high implants costs. Hence, this research explored the potential of an inexpensive biogenic HA derived from fish scales and FsHA/yttria-stabilized zirconia (YSZ) bioceramic coatings on a Ti–6Al–4V alloy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…It can be seen in the high-magnification images that the apatite precipitates were composed of flaky or plate-like crystals. Therefore, the HA samples prepared in this study via the hydrothermal method with and without the mulberry leaf extract demonstrated better bioactivity, which is an essential requirement for artificial materials to bond to living bones in the living body [ 41 ]. Since SBF has similar ion concentrations to the inorganic components in human plasma, biomineralization studies in SBF can demonstrate the similarity between the in vitro and in vivo behavior of bioceramics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen in the high-magnification images that the apatite precipitates were composed of flaky or plate-like crystals. Therefore, the HA samples prepared in this study via the hydrothermal method with and without the mulberry leaf extract demonstrated better bioactivity, which is an essential requirement for artificial materials to bond to living bones in the living body [ 41 ]. Since SBF has similar ion concentrations to the inorganic components in human plasma, biomineralization studies in SBF can demonstrate the similarity between the in vitro and in vivo behavior of bioceramics.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen in the high-magnification images that the apatite precipitates were composed of flaky or plate-like crystals. Therefore, the HA samples prepared in this study via the hydrothermal method with and without the mulberry leaf extract demonstrated better bioactivity, which is an essential requirement for artificial materials to bond to living bones in the living body [41]. Since SBF has similar The samples of HA synthesized via the hydrothermal reaction at 150 • C for 24 h with (H1t2M) and without (H1t2) the addition of the mulberry leaf extract were subjected to cell culturing for 1 and 4 days.…”
Section: Bioactivity and Biocompatibility Of The As-prepared Ha Samplementioning
confidence: 95%